Old Testament figures in art - De Capoa, Chiara; Zuffi, Stefano, 1961- (Los Angeles : J. Paul Getty Museum, 2003)
Throughout the Middle Ages, sacred Christian art had two objectives: to express veneration for God and to provide illustrative lessons on the Christian faith to a largely illiterate population. Continuing in the spirit of the other books in this series, Old Testament Figures in Art compiles entries on key figures and events in the Old Testament, beginning with the Pentateuch, then drawing from the historical books, the books of wisdom and poetry, and, finally, the prophetic books.
From the creation to the Tower of Babel -- Story of Abraham -- Story of Jacob -- From Egypt to the Promised Land -- David and Solomon -- Stories and heroes of the Israelites -- Wise men and prophets.
Includes indexes.
Keywords: Bible -- Illustrations; Christian art and symbolism; Illustrated works